The Use of Grammar-Translation Method in Teaching Reading at the 9th Grade Students of SMPN 2 Tanjung Raya - Ary, Ari Hidayat (BiCED Proceeding, 2024)
This research was done at SMPN 2 Tanjung Raya. This research was conducted to analize the use of GTM in Teaching Reading at the 9th Grade Students of SMPN 2 Tanjung Raya by the English teacher. As the result, the researcher want to analyze is there the accordance between teacher’s implementation of GTM in teaching reading with the theory provided by the expert or not.The implementation was observed during teaching reading with the theme narrative text. The design of this research was descriptive qualitative research with the observation and interview as the instrument of this research.The observation was done three times with the different sub-theme of teaching reading material. The interview session was also done once in order to strengthen the data from observation. There were twelve questions related to the use of GTM in teaching reading for the teacher. There English teacher of the 9th.1 grade students be the informant of this research. The result of the research showed that from totally nine techniques of GTM provided by Larsen, only seven techniques done by the teacher. Those techniques are translating the literary passage, reading comprehension questions, deductive application of the grammar rules, fill in the blank, memorized the vocabulary, used words in sentences, and composition. On the other hand, there were two techniques did not do by the teacher. Those techniques are finding cognates and finding synonym and antonym. The teacher let these two techniques because they had no enough time. Although the teacher did not do all techniques of GTM, however the use of seven techniques was accordance to the theory from Larsen.